A symptomatic atherosclerotic persistent pharyngo-hyo-stapedial artery: Treatment management and embryological considerations - Cagnazzo, Federico (Interv Neuroradiol, 2020)
The stapedial artery (SA) is an embryonic vessel connecting the internal carotid artery (ICA) to the branches of the future external carotid artery (ECA). It passes through the primordium of the stapes that progressively develops around the SA. Normally, SA disappears during the tenth week in utero. Approximately 0.4% of the population can have a persistent SA. It can persist as four types of embryological variations, of which the pharyngo-hyo-stapedial variant has been rarely described before. We reported a case of a 61-year-old woman presented with transient ischemic attacks (TIAs). Computed tomography angiography showed an unusual “duplicated” aspect of the left ICA. Digital subtraction angiography depicted a persistent pharyngo-hyo-stapedial artery with an atherosclerotic wall and was considered the cause of the TIAs. After failure of the antiplatelet therapy in preventing recurrent TIAs, stenting of the artery was planned and successfully performed. Patient was asymptomatic during 12-month follow-up. The pharyngo-hyo-stapedial artery is a very rare variation in which the SA is supplied by the inferior tympanic (rising from the ascending pharyngeal artery) and the hyoid artery (rising from the ICA). To our knowledge, this is a unique case of a pharyngo-hyo-stapedial artery in a patient presenting associated ischemic symptoms. Radiological and embryological findings are discussed.